2017
DOI: 10.1016/j.jad.2017.03.075
|View full text |Cite
|
Sign up to set email alerts
|

High frequency repetitive transcranial magnetic stimulation treatment for major depression: Dissociated effects on psychopathology and neurocognition

Abstract: High frequency repetitive transcranial magnetic stimulation treatment for major depression: dissociated effects on psychopathology and neurocognition 2 ABSTRACTObjective: This open-label pilot study explored the potential effects of High frequency repetitive transcranial magnetic stimulation (HF-rTMS) on two neurocognitive domains (decisionmaking and impulse control) in adult patients diagnosed with Major Depressive Disorder (MDD).Method: Subjects with a diagnosis of MDD (n=24) underwent HF-rTMS targeted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Both protocols produced global improvement in severity and symptoms of BPD, particularly in impulsiveness, affective instability, and angerNRYesDurmaz O, 20174236 rTMSMDDOpen-labelLeft DLPFC1520 Hz1000110% of RMTHRSATo evaluate the efficacy of rTMS in patients with treatment-resistant major depressionThe findings suggested that comorbid anxiety symptoms, particularly somatic anxiety, could predict the response to rTMS in treatment-resistant major depressive disorderHeadache in eight patients, dizziness in four patients, and lacrimation in three patients. Only one patient dropped out of the study due to side effects or intoleranceYesNoh TS, 20174317 rTMSTinnitusRCTLeft auditory cortex (AC) and left DLPFC or only the left DLPFC41 Hz2000 or 3000110% of RMTSTAIWe evaluated treatment outcomes following single-site rTMS in the DLPFC and dual-siterTMS in the AC and DLPFCGroup 1 exhibited significant improvements in scores on the STAI for both state anxiety and trait anxiety at 12 weeks posttreatment.Group 2 showed an improvement in only the STAI-X2 score at 12 weeks posttreatment.NRNoTovar-Perdomo S, 20174424 rTMSMDDOpen-label, pilot studyLeft DLPFC2010 Hz3000120% of RMTBAITo explore the effects of a course of accelerated high-frequency rTMS on two neurocognitive domains in patients with MDDDepression and anxiety scores significantly improved from pre-post HF-rTMS treatment.The absence of practice effects in our longitudinal design raises the possibility that rTMS may also have cognitive side effects which, like antidepressant effects, may recede and reveal cognitive improvements after treatment cessation and sustained recoveryNoElbeh KAM, 2016630 rTMS/15 shamOCDRCTRight DLPFC + left DLPFC101 Hz or 10 Hz200 or 500…”
Section: Resultsmentioning
confidence: 99%
“…Both protocols produced global improvement in severity and symptoms of BPD, particularly in impulsiveness, affective instability, and angerNRYesDurmaz O, 20174236 rTMSMDDOpen-labelLeft DLPFC1520 Hz1000110% of RMTHRSATo evaluate the efficacy of rTMS in patients with treatment-resistant major depressionThe findings suggested that comorbid anxiety symptoms, particularly somatic anxiety, could predict the response to rTMS in treatment-resistant major depressive disorderHeadache in eight patients, dizziness in four patients, and lacrimation in three patients. Only one patient dropped out of the study due to side effects or intoleranceYesNoh TS, 20174317 rTMSTinnitusRCTLeft auditory cortex (AC) and left DLPFC or only the left DLPFC41 Hz2000 or 3000110% of RMTSTAIWe evaluated treatment outcomes following single-site rTMS in the DLPFC and dual-siterTMS in the AC and DLPFCGroup 1 exhibited significant improvements in scores on the STAI for both state anxiety and trait anxiety at 12 weeks posttreatment.Group 2 showed an improvement in only the STAI-X2 score at 12 weeks posttreatment.NRNoTovar-Perdomo S, 20174424 rTMSMDDOpen-label, pilot studyLeft DLPFC2010 Hz3000120% of RMTBAITo explore the effects of a course of accelerated high-frequency rTMS on two neurocognitive domains in patients with MDDDepression and anxiety scores significantly improved from pre-post HF-rTMS treatment.The absence of practice effects in our longitudinal design raises the possibility that rTMS may also have cognitive side effects which, like antidepressant effects, may recede and reveal cognitive improvements after treatment cessation and sustained recoveryNoElbeh KAM, 2016630 rTMS/15 shamOCDRCTRight DLPFC + left DLPFC101 Hz or 10 Hz200 or 500…”
Section: Resultsmentioning
confidence: 99%
“…While George et al (2014) allowed continuing medication regimens, which may have affected the results, Desmyter et al (2016) included only antidepressant-free participants, which in turn limits the interpretation and generalizability of results in real-life emergency room suicidal patients, who frequently must be maintained on pharmacologic treatments. In general, participants appeared to continue antidepressant medication regimens in all openlabel studies (Dardenne et al, 2018;Holtzheimer III et al, 2010;McGirr et al, 2015;Tor et al, 2016;Tovar-Perdomo et al, 2017;Williams et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation parameters and sample characteristics are summarized in Table 1 and Table 2, respectively. Ten publications meeting inclusion criteria were derived from shared samples; 4 from a larger rTMS study (Baeken et al, 2013;Baeken et al, 2014;Baeken et al, 2015;Baeken et al, 2017b), 4 from a larger intermittent TBS (iTBS) study (Baeken et al, 2017a;Desmyter et al, 2016;Duprat et al, 2016;Duprat et al, 2017), and 2 from an open-label rTMS study (McGirr et al, 2015;Tovar-Perdomo et al, 2017). Randomized controlled trials (RCTs) included a total of 301 unique patients.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of rTMS over the dlPFC also has effects on the cognitive control network and affects associated with cognitive control processes ( Lantrip et al, 2017 ). However, measures of decision-making and impulse control were not affected by the application of rTMS over the left dlPFC, though measures of depression and anxiety both showed significant improvement ( Tovar-Perdomo et al, 2017 ). This finding suggests that neurocognition may not be related to the psychopathological symptoms observed in these mood disorders.…”
Section: Affective Processing Of Tms Over the Pfc In Depressionmentioning
confidence: 99%